Emergency Preparedness Law and Willingness to Respond in the EMS Workforce. Issue 4 (21st July 2014) - Rutkow, Lainie; Vernick, Jon S.; Thompson, Carol B.; Pirrallo, Ronald G.; Barnett, Daniel J.
Abstract Introduction For effective responses to emergencies, individuals must have the ability to respond and also be willing to participate in the response. A growing body of research points to gaps in response willingness among several occupational cohorts with response duties, including the Emergency Medical Services (EMS) workforce. Willingness to respond is particularly important during an influenza or other pandemic, due to increased demands on EMS workers and the potential for workforces to be depleted if responders contract influenza or stay home to care for sick dependents. State emergency preparedness laws are one possible avenue to improve willingness to respond. Hypothesis Presence of certain state-level emergency preparedness laws (ie, ability to declare a public health emergency; requirement to create a public health emergency plan; priority access to health resources for responders) is associated with willingness to respond among EMS workers. Methods Four hundred twenty-one EMS workers from the National Registry of Emergency Medical Technicians' (NREMT's) mid-year Longitudinal EMT Attributes and Demographics Study (LEADS) were studied. The survey, which included questions about willingness to respond during an influenza pandemic, was fielded from May through June 2009. Survey data were merged with data about the presence or absence of the three emergency preparedness laws of interest in each of the 50 US states. Unadjusted logistic regression analyses were performed with the presence/absence of each law and were adjusted for respondents' demographic/locale characteristics. Results Compared to EMS workers in states that did not allow the government to declare a public health emergency, those in states that permitted such declarations were more likely to report that they were willing to respond during an influenza pandemic. In adjusted and unadjusted analyses, this difference was not statistically significant. Similar results were found for the other state-level emergency preparedness laws of interest. Conclusion While state-level emergency preparedness laws are not associated with willingness to respond, recent research suggests that inconsistencies between the perceived and objective legal environments for EMS workers could be an alternative explanation for this study's findings. Educational efforts within the EMS workforce and more prominent state-level implementation of emergency preparedness laws should be considered as a means to raise awareness of these laws. These types of actions are important steps toward determining whether state-level emergency preparedness laws have the potential to promote response willingness among EMS workers. <mixed-citation id="ref" publication-type="journal"> <string-name> <given-names>L</given-names> <x content-type="archive" xml:space="preserve"> </x> <surname>Rutkow</surname> </string-name>, <string-name><given-names>JS</given-names><x content-type="archive" xml:space="preserve"> </x><surname>Vernick</surname></string-name>, <string-name><given-names>CB</given-names><x content-type="archive" xml:space="preserve"> </x><surname>Thompson</surname></string-name>, <string-name><given-names>RG</given-names><x content-type="archive" xml:space="preserve"> </x><surname>Pirrallo</surname></string-name>, <string-name><given-names>DJ</given-names><x content-type="archive" xml:space="preserve"> </x><surname>Barnett</surname></string-name>. Emergency preparedness law and willingness to respond in the EMS workforce . <source>Prehosp Disaster Med</source>. <year>2014</year>;<volume>29</volume>(<issue>4</issue>):<fpage>1</fpage>-<lpage>6</lpage></mixed-citation>.